Informal investors in Chile: an exploratory study from a gender perspective - Romaní, Gianni; Atienza, Miguel; Amorós, José Ernesto (Journal of Business Economics and Management, 2012)
Informal investment represents one of the main sources to finance early-stage new ventures. Despite the progressive participation of women in informal investment, little is known about the characteristics of female informal investors, especially in developing countries. This study examines the gender differences of a sample of 613 informal investors in Chile. To this end we used the database from the Global Entrepreneurship Monitor Chile 2007–2008 and applied tests of differences in proportions and means for independent samples. The results show that there are significant gender differences in some socio-demographic variables, like education and work status, and also in the perception of good opportunities and the fear to failure. Additionally, women invest smaller amounts and expect lower returns than men do. Finally, women invest more than men in close family. Policy implications of these results are discussed. Article in English. Neformalių investuotojų (pagal lytį) tyrimas Čilėje Santrauka. Neformalios investicijos – vienas pagrindinių šaltinių, iš kurių finansuojamos naujai besikuriančios arba tik pradėjusios savo veiklą įmonės. Nepaisant to, kad neformalioje investicijų veikloje palaipsniui daugėja moterų, gana mažai žinoma apie jas kaip neformalias investuotojas, ypač besivystančiose šalyse. Autoriai atliko tyrimą Čilėje, kuriame dalyvavo 613 skirtingų lyčių investuotojų, kurie buvo paimti iš duomenų bazės „Global Entrepreneurship Monitor Chile 2007–2008 m“. Autorių atliktų tyrimų rezultatai rodo, kad vis dėlto kai kuriuose socialiniuose demografiniuose kintamuosiuose esama reikšmingų lyčių skirtumų, pavyzdžiui, išsilavinimas ir užimamos pareigos, perspektyvų darbovietėje suvokimas, karjera ir nesėkmės baimė. Atlikę tyrimą autoriai nustatė, kad moterys labiau linkusios investuoti mažesnes sumas nei vyrai. Reikšminiai žodžiai: neformalūs investitoriai, Čilė, lytis, finansavimas, veikla